Physiology and nutrition for amateur wrestling - Lambert, C. P. (CRC Press, 2021)
Physiology and Nutrition for Amateur Wrestling is essential reading for amateur wrestlers and their coaches with a desire to learn about physiological training and nutrition for their sport.